Enhancing Elementary Students’ Mastery of Basic Football Techniques Through Simulation and Role Play Methods - Ahmad Atiq; Fajar Vidya Hartono; Muhammad Ali; Witri Suwanto; Didik Purwanto (STAI Hubbulwathan Duri, 2024)
This study investigates the effectiveness of simulation and role-play methods in enhancing basic football techniques among elementary school students. A classroom action research approach was employed, involving 28 students from SD Mujahidin Pontianak. The study was conducted over two cycles, with pre- and post-intervention assessments of students' basic football techniques. The interventions utilized simulation and role-play methods, where students engaged in interactive activities to mimic or enact scenarios that develop football skills. Before the intervention, 6 students were categorized as 'less,' 22 as 'sufficient,' with an average score of 63.57, indicating a 'sufficient' proficiency level. Post-intervention, 1 student remained in the 'sufficient' category, while 27 were categorized as 'good,' achieving an improved average score of 79.71. This reflects an 11.26% increase in basic football techniques from cycle 1 to cycle 2. The findings demonstrate that simulation and role-play methods significantly enhance students' engagement and skill acquisition in football techniques. These interactive approaches promote active learning and practical skill application, leading to marked improvements in performance. Simulation and role-play methods effectively improve basic football techniques among elementary students. Teachers are encouraged to adopt these methods to foster skill development and active participation in physical education.